Second generation antihistamines: an update. Issue 4 (August 2019) - Sánchez-Borges, Mario; Ansotegui, Ignacio J.
Abstract : Purpose of review: This article presents an update on the clinical pharmacology, mechanisms of action, and safety of second generation antihistamines (SGAHs). Recent findings: Recent research has shown the efficacy and good tolerance of SGAHs supporting its indication as first line medications for the treatment of allergic rhinoconjunctivitis and urticaria. Summary: The information contained in this review is relevant for the correct utilization of SGAHs by practicing physicians who take care of these highly prevalent clinical disorders.